The frequency of pharmacological pain relief in university neonatal intensive care units - Prestes, Ana Claudia Yoshikumi; Guinsburg, Ruth; Balda, Rita C. X.; Marba, Sergio T. M.; Rugolo, Ligia Maria Suppo de Souza [UNESP]; Pachi, Paulo R.; Bentlin, Maria Regina [UNESP] (Fundacao Sociedade Brasileira de Pediatria, 2005)
Objective: To evaluate the use of drugs to relieve the pain of invasive procedures newborn infants cared for at a university hospital NICU. Methods: A prospective cohort study of all newborn infants hospitalized in four NICU during October 2001. The following data were collected: demographic data of the hospitalized newborn infants; clinical morbidity; number of potentially painful procedures and frequency of analgesic administration. Factors associated with the use of analgesia in this cohort of patients were studied by multiple linear regression using SPSS 8.0. Results: Ninety-one newborn infants were admitted to the NICU during the study period (1,025 patient-days). Only 25% of the 1,025 patient-days received systemic analgesia. No specific drugs were administered to relieve acute pain during any of the following painful events: arterial punctures, venous, capillary and lumbar punctures or intubations. For chest tube insertion, 100% of newborn infants received specific analgesia. For the insertion of central catheters 8% of the newborn infants received painkillers. Only nine of the 17 newborn infants that underwent surgical procedures received any analgesic dosage during the postoperative period. For 93% of patients under analgesia the drug of choice was fentanyl. The presence of mechanical ventilation increased the chance of newborn infants receiving painkillers by 6.9 times and the presence of chest tube increased this chance by five times. Conclusion: It is necessary to train health professionals in order to bridge the gap between scientific knowledge regarding newborn infant pain and clinical practice. Copyright © 2005 by Sociedade Brasileira de Pediatria.
Keywords: Acute pain; Analgesia; Neonatal intensive care unit; Newborn infant; Pain; fentanyl; analgesia; artery puncture; artificial ventilation; catheter; child care; controlled study; demography; female; hospitalization; human; infant; intensive care unit; intubation; lumbar puncture; major clinical study; male; morbidity; multiple linear regression analysis; pain; postoperative period; tube; vein puncture